Pengaruh Struktur Modal Terhadap Return On Equity (ROE) Pada PT. Summarecon Agung, Tbk - Muhibah Rustam (Movere Journal, 2019)
The purpose of the study was to analyze the impact of capital structure on return on equity (ROE) at PT. Summarecon Agung, Tbk. The type of data used in this study are quantitative and qualitative data. The data source used is secondary data. This study employed the descriptive analysis and a regresion analysis of panel data. The result of study showed that the capital structure showed a positive and not significant effect on return on equity (ROE), the regresion analysis showed Y = -154,79 + 17,31X, the r value of 0,35 which indicates a weak relationship between capital structure and return on equity. R2 of 12,25% which indicates return on equity (ROE) is determined by capital structure and return by other factors not in accordance in this study. The value of thitung (0,75) < ttabel (2,78) shows that capital structure has no significant effect on return on equity (ROE). Keywords : capital structure, return on equity (ROE)